Optimisation studies on inclined web wheel using finite elements - 269577 Ng, Gheok Kuan (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1999